Stem Cell Modeling of Core Binding Factor Acute Myeloid Leukemia - Federico Mosna; Michele Gottardi (Hindawi Limited, 2016)
Even though clonally originated from a single cell, acute leukemia loses its homogeneity soon and presents at clinical diagnosis as a hierarchy of cells endowed with different functions, of which only a minority possesses the ability to recapitulate the disease. Due to their analogy to hematopoietic stem cells, these cells have been named "leukemia stem cells," and are thought to be chiefly responsible for disease relapse and ultimate survival after chemotherapy. Core Binding Factor (CBF) Acute Myeloid Leukemia (AML) is cytogenetically characterized by either the t(8;21) or the inv(16)/t(16;16) chromosomal abnormalities, which, although being pathognomonic, are not sufficient per se to induce overt leukemia but rather determine a preclinical phase of disease when preleukemic subclones compete until the acquisition of clonal dominance by one of them. In this review we summarize the concepts regarding the application of the "leukemia stem cell" theory to the development of CBF AML; we will analyze the studies investigating the leukemogenetic role of t(8;21) and inv(16)/t(16;16), the proposed theories of its clonal evolution, and the role played by the hematopoietic niches in preserving the disease. Finally, we will discuss the clinical implications of stem cell modeling of CBF AML for the therapy of the disease.